SKILLS OF STRENGTHENING PHYSICAL HEALTH THROUGH TAEKWON-DO ITF EXERCISES - Aziz Tulkunovich Ibragimov; Doniyor Bakhtiyorovich Kamolov (Proximus Journal Publishing, 2025)
Taekwon-Do ITF is a traditional Korean martial art that combines physical discipline with mental development. In recent years, the role of Taekwon-Do ITF in improving physical health has gained attention in the context of modern fitness and sports science. This article explores how ITF training methods contribute to the development of strength, flexibility, endurance, and overall physical well-being. Emphasis is placed on the physiological and psychological benefits of regular Taekwon-Do practice, supported by academic studies and expert insights. The focus is on the implementation of ITF techniques among university students in Uzbekistan, analyzing the practical outcomes of its integration into sports education. This paper also outlines key methodological approaches, research findings, and provides an in-depth discussion on the long-term benefits of ITF for maintaining physical health
Keywords: Taekwon-Do ITF; physical health; martial arts; strength